Property rights for social inclusion: Migrant strategies for securing land and livelihoods in Papua New Guinea - Koczberski, Gina; Curry, George; Imbun, B. (Blackwell Publishers, 2009)
This paper examines the broad range of informal land transactions and arrangements migrants are entering into with customary landowners to gain access to customary land for export cash cropping in the oil palm belt of West New Britain, Papua New Guinea. Whilst these arrangements can provide migrants with relatively secure access to land, there are instances of migrants losing their land rights. Typically, the land tenure arrangements of migrants with more secure access to land are within a framework of property rights for social inclusion whereby customary landowners’ inalienable rights to land are preserved and the ‘outsider’ becomes an ‘insider’ with ongoing use rights to the land. Through socially embedding land transactions in place-based practices of non-market exchange, identities of difference are eroded as migrants assume identities as part of their host groups. This adaptability of customary land tenure and its capacity to accommodate large migration in-flows and expanding commodity production undermines the argument common amongst proponents of land reform that customary tenure is static and inflexible. Before such claims are heeded, there must be more detailed empirical investigations of the diverse range of land tenure regimes operating in areas of the country experiencing high rates of immigration.